Occurrence of Hashimoto thyroiditis among the first- and second-degree relatives of systemic lupus erythematosus patients with Hashimoto thyroiditis - L. Carli; C. Tani; S. Vagnani; F. Querci; C. Baldini; R. Talarico; A. Della Rossa; S. Bombardieri; M. Mosca (PAGEPress Publications, 2013)
Not available